Pengaruh Edukasi Gizi terhadap Pengetahuan Siswa SMAN di Banjarmasin - Linda Kusumawati; Anita Herawati; Muhammad Ali Yasir (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Adolescence is a crucial phase in the human life cycle, marked by continuous growth and maturation. During this period, various physical and biological changes occur that directly impact the health and nutritional status of adolescents. An imbalance between adequate and inadequate intake can lead to nutritional problems, both overnutrition and undernutrition. Therefore, measures are needed to improve knowledge, understanding, and awareness of proper nutrition. To determine whether there is an effect on improving nutrition knowledge in students before and after health interventions. This research is an experimental study using a pre-experimental design. The research design used a one-group pretest-posttest design. The study population was 36 students from SMAN Banjarmasin. Based on the Wilcoxon signed-rank test, a p-value of 0.000 was obtained, with a p-value <0.05. Therefore, Ha is accepted and Ho is rejected. Therefore, it can be concluded that there is a significant difference between the pretest and posttest implementation of the nutrition education method.Health education about nutrition for students of SMAN Banjarmasin resulted in an increase in knowledge about nutrition, nutritional status, BMI, and nutritional problems in students, namely in the categories of good knowledge and sufficient knowledge and there were no more who had insufficient knowledge and had a positive impact on the knowledge of students of SMAN Banjarmasin